Dosimetry and optimal scan time of (18F)SiTATE-PET/CT in patients with neuroendocrine tumours - Beyer, Leonie; Gosewisch, Astrid; Lindner, Simon; Völter, Friederike; Mittlmeier, Lena M.; Tiling, Reinhold; Brendel, Matthias; Cyran, Clemens C.; Unterrainer, Marcus; Rübenthaler, Johannes; Auernhammer, Christoph J.; Spitzweg, Christine; et al. (European journal of nuclear medicine and molecular imaging, 2021)
Radiolabelled somatostatin analogues targeting somatostatin receptors (SSR) are well established for combined positron emission tomography/computer tomography (PET/CT) imaging of neuroendocrine tumours (NET). [18F]SiTATE has recently been introduced showing high image quality, promising clinical performance and improved logistics compared to the clinical reference standard 68Ga-DOTA-TOC. Here we present the first dosimetry and optimal scan time analysis.